Applying Outdoor Environment to Develop Health, Comfort, and Energy Saving in the Office in Hot-Humid Climate - Rong Chen; Wen-Pei Sung; Hung-Chang Chang; Yi-Rou Chi (The Scientific World Journal)
A human life demand set to emerge in the future is the achievement of sustainability by maintaining a comfortable indoor environment without excessive reliance on energy-consuming air conditioners. The major research processes in this study are: (1) measuring indoor air quality and thermal comfort to evaluate the comfort of an indoor environment; (2) implementing questionnaire survey analysis to explore people’s environmental self-perceptions and conducting a meta-analysis of the measurement results for air quality and physical aspects; and (3) constructing an indoor monitoring and management system. The experimental and analysis results of this research reveal that most of the office occupants preferred a cooler environment with a lower temperature. Additionally, because the summers in Taiwan are humid and hot, the occupants of an indoor space tend to feel uncomfortable because of the high humidity and poor indoor air quality. Therefore, Variable Air Volume (VAV), two air intakes, and exhaust plant are installed to improve indoor environment. After improvement, a lower temperature (approximately 21.2–23.9°C) indirectly reduces humidity, thereby making the occupants comfortable. Increasing air velocity to 0.1~0.15 m/s, the carbon dioxide concentrations decrease below the requirement of the WHO. Ninety-five percent of the workers corresponded to the standard comfort zone after this improvement.